Use of parabolic troughs in HVAC applications – Design calculations and analysis - Khaled Chahine (Case Studies in Thermal Engineering, 2018)
The present work is concerned with the combination of solar energy systems with HVAC systems. Namely, the objective is finding a way of applying green energy concepts to HVAC systems. Particularly, solar concepts are employed to supply electrical power to HVAC systems. Hence, an innovative concept that permits the use of electrical energy provided by parabolic troughs to drive electrical components of the HVAC system is suggested. Thermal modeling along with governing equations of electricity production from parabolic troughs are presented. Calculations of the electrical power needed for HVAC system, showed that an order of magnitude of energy saving is attainable. Finally, the aforementioned concept was applied on a genuine case in Beirut city. It was shown that four mirrors with a 0.5 efficiency of the storage system are capable to drive the pumps of a HVAC system of a 4-floor building all over the year. Keywords: Parabolic trough, HVAC, Energy management, Solar energy, Electrical power, Saving energy